Guarda dos filhos e mediação familiar: a experiência inglesa contribuindo para uma mudança sistêmica no Brasil - Beraldo, Anna de Moraes Salles (2015)
In the context of recent decades, it was observed that the residence order was commonly given to the mother, and to the father only in exceptional cases. To the male parent it usually remained the right to biweekly "visits" and the child s financial support. This resulted in disencouraging the strengthening of the paternal-filial relationship. Thus, the aim of the thesis was to question whether the judicial decisions concerning the child arrangements order would effectively meet the child's best interest. Moreover, it questioned if these decisions are able to break the conflictual dynamics. The hypothesis is that in matters relating to family law and, more precisely, in the conflicts involving children and teenagers, the court decision is not the most appropriate way. The choice of the subject is justified given that currently the parental roles are no longer so strictly defined, with the women entering the labour market and, in parallel, the father's search for a more active role in their children's lives. Therefore, given the breakdown of the relationship of the parents, it must be chosen a family arrangement, covering the constitutional principles of the best interests of the child and responsible parenthood. This thesis was based in legislative, doctrinal and jurisprudential analysis, as well as a substantial part of its research conducted in England, where significant changes relating to parental responsibility have occured in recent years, which may be relevant to Brazil. The results of this study demonstrate the importance of using other means, not only the court for the maintenance and strengthening of emotional bonds due to the transformation of that nuclear family. In this sense, conflict mediation and collaborative practice can greatly assist parents in such troubled times that is the disruption of the relationship. This is another approach that seeks to focus on the responsibility of parents and common interests, rather than on the logic of seeking to blame the responsible for the relationship breakdown. Moreover, the mere enactment of laws on child arrangements order without a systemic change that involves society and the State will not provide representative advances